(untitled) (Rupandehi Campus Journal, 2024)
The present research investigates the role of mass media in producing the narratives of climate change and climate justice in Nepal. For this purpose, sample of the date were extracted from the online edition of The Kathmandu Post daily, the largest circulating English newspaper of Nepal. The study has used Critical Discourse Analysis as the methodological tool to analyze socio-cognitive as well as linguistic elements prevalent in the texts of the newspaper. Particularly, through the philosophical impetuses of Norman Fairclough and Teun A. Van Dijik we have tried to unveil the power dynamics imbedded into the text. Our findings reveal that, the mass media play important role in shaping the meaning of climate justice and this is executed through linguistic as well as pictorial representation of climate change. When the mass media intend to serve the interest of the state that further exacerbates the climate change induced sufferings of the marginalized community.